Navigating LGBT+ ageing inequalities during challenging times - Hafford-Letchfield, Trish (Socialno delo, 2022)
The COVID-19 pandemic has had a significant impact on older people’s lives on a global scale but for some marginalised communities have seen a marked exacerbation of health and other inequalities. Research has highlighted the impact of the pandemic on lesbian, gay, bisexual and trans (LGBT+) people’s lives, but less has been documented about the experiences of LGBT+ older communities and how their specific needs have been mediated. Community-based advocacy organisations are central to promoting LGBT+ human rights in the UK through its social movements, and this paper explores their role and significance during a distinct period of the UK mandatory isolation. Drawing on a case study approach based on qualitative interviews with six key LGBT+ community organisations in the UK, we captured their insights into how they navigated support for older people when faced with limited resources and the challenges posed by mandatory physical and social distancing. We position these events in current discourse about structural and health inequalities for LGBT+ ageing in the UK.
Keywords: advocacy; COVID-19; človekove pravice; human rights; mandatory isolation; obvezna izolacija; zagovorništvo